Números metálicos - Huber, Adriane Vaz (2019)
This work is a bibliographic study based on books, articles and dissertations dealing with metallic numbers. The objective is to study the metallic numbers with the use of quadratic equations, recurrence relations, representations in continuous fractions, geometric constructions and sequences by radicals. To do so, we did initially a historical study on the gold number and Fibonacci sequences. We study the relations of second order recurrence and continuous fractions simples, after which, with the definition of metallic numbers, we relate them to these concepts. We also did the relation of the metallic numbers with the geometric constructions and with the sequences of continuous radicals and we suggest possibilities of applications in the Basic Education.